Inventory of the of St. Peter Church in the Antakalnis written by Peter Korkonos in 1609 - Pietrzkiewicz, Iwona (Bibliotheca Lituana, 2012)
In 1609 Peter Korkonos, the new rector (parish priest) of the St. Peter Church in Vilnius wrote an inventory of this church. It’s the oldest inventory of the church we know today. Two fragments of this document have been found in the collections of the Archive of Vilnius Archdiocese and The Martynas Mažvydas National Library of Lithuania. In this edition these two fragments of the historical source have been combined and commented. Particular attention has been paid to the problem of books, which were the property of the church at this time. The most relevant facts from the history of St. Peter Church are also mentioned in this work. The first wooden church founded about 1492–1507 burned down. The management of the parish and the years of restoration were documented by Peter Korkonos. After the death of the parson St. Peter Church was handed over to the Canons Regular of the Lateran. The presented sources have not been widely used in academic theses concerning the church. They complete former knowledge related with formation of the local library.
Keywords: none